PENGARUH CITRA MEREK DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN HONDA VARIO DI PT. ASTRA BRAWIJAYA MATARAM - I Gusti Ayu Devi Cintaningtyas; I Made Suardana; Nendy Pratama Agusfianto (Valid: Jurnal Ilmiah, 2018)
This research is to test the brand of Citra and circular influence so that the variable of research are 2 independence variables: brand of Citra (X1) and circular (X2) and the dependent variable is decided of buying (Y). The population of this research is a consumer who buys Honda Vario at PT. Astra Brawijaya Mataram and it is unknown numbers, this sample was taken by using purposive sampling. The criterion of this sample is a consumer who is from Mataram and who has been upper 20 years old. Data was gotten by spraying 60 questioners to the respondent who buying Honda Vario at PT. Astra Brawijaya Mataram. Data is analyzed by using Regresi Linear Berganda, this result shows that brand of Citra variable has T count is bigger than T table, it is 5,665>2,00247. Which can be said that the variable brand of citra was significant influenced at the decision of buying at PT. Astra Brawijaya Mataram. The variable of circular has T count is bigger than T table, it is 4,451>2,00247. It can be said that the variable of circular is significant influenced decision of buying at PT. Astra Brawijaya Mataram. The result of testing simultantly shows that F count is bigger than F table. It is 140,176>3,16. This means that the variable of citra brand and circular is significant influenced simultantly to the buying decition Honda Vario at PT. Astra Brawijaya Mataram. Meanwhile, the result of analysis to the koefisien determination (R square) is 0,825. This means the next variable is fritter at R square as much as 0,175 is influence of another variable which is not included in researching